Modified Shape Functions for Specht's Plate Bending Element (Journal of Computational Mathematics, 1994)
In this paper we discuss Specht's plate bending element, give the relationships between $∫_{F_ρ} wds \ {\rm or} \ ∫_{F_ρ} \frac{∂w}{∂n} ds$ and the nodal parameters (or freedoms of degrees), further light on the construction methods for that element and at last introduce a new plate bending element with good convergent properties.